Development of transversal skills in higher education programs in conjunction with online learning: relationship between learning strategies, project-based pedagogical practices, e-learning platforms, and academic performance - Yolanda Guerra-Macías; Sergio Tobón (Heliyon)
This study investigates the development of transversal skills and their association with academic performance in university students enrolled in on-campus programs with online activities. A cross-sectional, descriptive, and quantitative research was conducted with 252 students from a public university in Mexico. Transversal skills, socioformative project-based practices, learning strategies, and the relevance of online activities were assessed using validated rubrics. The results indicated a low level of development in three transversal skills: research, entrepreneurship, and English, with the latter being the poorest rated. Critical and creative thinking exhibited the highest level of development. In the didactic component, socioformative project-based pedagogical practices and learning strategies showed acceptable levels. Students expressed satisfaction with complementary online activities, showing a preference for interactive videos and short videos under 4 min. Regression analysis and structural equations were used to examine the relationships between various factors. Results demonstrated that socioformative project-based pedagogical practices, learning strategies, and online education positively correlated with the development of transversal skills. Furthermore, a higher level of transversal skills was associated with better academic averages among students. Socioformative project-based pedagogical practices also correlated with academic performance through transversal skills. The study concludes that integrating online activities into on-campus programs, based on the socioformative pedagogical model, can enhance the development of transversal skills and improve academic performance. Further research into the implementation of this educational model and its long-term impact on university education and professional success is recommended.